2010
DOI: 10.1038/cr.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of divalent metal transporter 1 in 6-hydroxydopamine intoxication is IRE/IRP dependent

Abstract: Iron plays a key role in Parkinson's disease (PD). Increased iron content of the substantia nigra (SN) has been found in PD patients, and divalent metal transporter 1 (DMT1) has been shown to be up-regulated in the SN of both MPTP-induced PD models and PD patients. However, the mechanisms underlying DMT1 up-regulation are largely unknown. In the present study, we observed that in the SN of 6-hydroxydopamine (6-OHDA)-induced PD rats, DMT1 with the iron responsive element (IRE, DMT1+IRE), but not DMT1 without IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
84
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 44 publications
13
84
1
Order By: Relevance
“…VPS35 is also responsible for divalent metal transporter 1 transport [224]. Mutated VPS35 may, therefore, lead to divalent metal transporter 1 missorting and iron accumulation, similar to the iron accumulation described in PD patients and in the 6-OHDA mouse model of PD [225]. Finally, VPS35 is also hypothesized to influence the Wnt signaling pathway via deficient sorting of the Wntless protein, which leads to Wntless degradation [226][227][228] and Wnt/b-catenin signaling is impaired in 6-OHDA-lesioned rats [229] and MPTP-induced mouse and monkey models [230].…”
Section: Vps35 (Park17)mentioning
confidence: 84%
“…VPS35 is also responsible for divalent metal transporter 1 transport [224]. Mutated VPS35 may, therefore, lead to divalent metal transporter 1 missorting and iron accumulation, similar to the iron accumulation described in PD patients and in the 6-OHDA mouse model of PD [225]. Finally, VPS35 is also hypothesized to influence the Wnt signaling pathway via deficient sorting of the Wntless protein, which leads to Wntless degradation [226][227][228] and Wnt/b-catenin signaling is impaired in 6-OHDA-lesioned rats [229] and MPTP-induced mouse and monkey models [230].…”
Section: Vps35 (Park17)mentioning
confidence: 84%
“…Our previous studies showing that DMT11IRE downregulation could be initiated by IRP1 knockdown may further confirm this notion. 8 Abnormal cerebral perfusion occurs in PD. 9 Hypoxia and other factors have been reported to suppress IRP/IRE binding affinity and to induce the downregulation of IRPs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that RA could protect MES23.5 dopaminergic cells against 6-OHDA- [105] or MPP + [106] -induced neurotoxicity in vitro and achieve neurorescue effects in 6-ODHA-lesioned rat model of PD in vivo [107] . (2) RA has an early renal protective role in nephritic damage.…”
Section: Other Pharmacological Findingsmentioning
confidence: 99%